(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The article discusses hygienic requirements in maxillary dental implantation, including pre- and postoperative sanitary measures, aseptic and antiseptic protocols, and the impact of oral hygiene on implant success. Based on clinical observations and literature review, enhanced hygienic control significantly reduces peri-implantitis and postoperative complications.